From Teachers' Professional Learning Communities to Mobile Networked Learning Communities: An Additional Path to the Integration of Gender Education into Medical Education - Hsing-Chen Yang; Ya-Chu Fu (National Taipei University of Education, 2021)
This article discussed the challenges in the establishment of teachers' professional learning communities aimed at integrating gender into medical education, including taking actions in response to the COVID-19 pandemic, and to identify opportunities in the challenging time. This article described the process a teacher learning community transformed into a mobile networked learning community. The process, divided into three distinctive acquisitions, are as follows: 1) Establish online platforms as knots for community interaction and mobile learning to address the diverse learning goals and individual learning needs of community members. 2) Include students as community participants to reinterpret learner-centered communities and pedagogical imaginary, establish new network relationships, and respond to community spirit in relation to learning. 3) Promote a new method for community participation, combine social network tools with mobile learning functions, and incorporate real-time online interaction. This article proposed the idea of inclusive learning in the university teachers' professional learning community, promoting "inclusiveness" instead of "homogeneousness" in the community to cover the goals and commitments of different members in terms of the practice of integrating gender into medical education and healthcare. This article also revealed the knots and connections between online platforms and offline in-person classes; these knots and connections conformed to the day-to-day teaching and learning of community members and provided an additional path to integrate gender into medical education and develop learning communities.